The circumcenter of a triangle is the center of a circumference where the three vertex are included. So basically we must find the circumference that passes through points O, V and W. The equation of a circumference of a radius r and a central point (a,b) is:
![(x-a)^2+(y-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ilekd9w5v3ytefhk3unvr8rhka2u3mptc6.png)
We have three points which give us three pairs of (x,y) values that we can use to build three equations for a, b and r. Using point O=(6,5) we get:
![(6-a)^2+(5-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/ph1f9ira1pg552l0ekc54i8opu9v0ifhh6.png)
Using V=(0,13) we get:
![(0-a)^2+(13-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/olz2ocu56o1nymk9js7bnhk3rg6o86r43c.png)
And using W=(-3,0) we get:
![(-3-a)^2+(0-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/oyiyz7zu3f9qjiglwet5u8a40scyfczg6b.png)
So we have a system of three equations and we must find three variables: a, b and r. All equations have r^2 at their right side. This means that we can take the left sides and equalize them. Let's do this with the second and third equation:
![\begin{gathered} (0-a)^2+(13-b)^2=(-3-a)^2+(0-b)^2 \\ a^2+(13-b)^2=(-3-a)^2+b^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/craot2746bkv8fn4d6g0m3uowai00gw0wv.png)
If we develop the squared terms:
![a^2+b^2-26b+169=a^2+6a+9+b^2](https://img.qammunity.org/2023/formulas/mathematics/college/70vyk4k2w4wxnwpqv3ywks3l4nqnc5mvtj.png)
Then we substract a^2 and b^2 from both sides:
![\begin{gathered} a^2+b^2-26b+169-a^2-b^2=a^2+6a+9+b^2-a^2-b^2 \\ -26b+169=6a+9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/thqfilxgilygsh8f2gca0bbo54ncpypxxt.png)
We substract 9 from both sides:
![\begin{gathered} -26b+169-9=6a+9-9 \\ -26b+160=6a \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ks0o4jzlgjgl5zyqfv4zgv4nxjzr4sqg0h.png)
And we divide by 6:
![\begin{gathered} (-26b+160)/(6)=(6a)/(6) \\ a=-(13)/(3)b+(80)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a2xeavu35pt0b7hyf2t9bwzgzhpdb4bhaf.png)
Now we can replace a with this expression in the first equation:
![\begin{gathered} (6-a)^2+(5-b)^2=r^2 \\ (6-(-(13)/(3)b+(80)/(3)))^2+(5-b)^2=r^2 \\ ((13)/(3)b-(62)/(3))^2+(5-b)^2=r^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1e08o4z15p7bek9zr4e8ly2tyt9qke5m4b.png)
We develop the squares:
![\begin{gathered} ((13)/(3)b-(62)/(3))^2+(5-b)^2=r^2 \\ (169)/(9)b^2-(1612)/(9)b+(3844)/(9)+b^2-10b+25=r^2 \\ (178)/(9)b^2-(1702)/(9)b+(4069)/(9)=r^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p3buv8fn23fcrds7vp823zp4fn7fvcvdgq.png)
So this expression is equal to r^2. This means that is equal